STUDENTS’ ERROR ANALYSIS IN USING QUESTION TAG ON TENTH GRADE STUDENTS AT SMK YAPIM BIRU- BIRU - Panjaitan, Indah Lestari (Jurnal Bahasa Indonesia Prima (BIP), 2019)
This study aims to inform the capability of students in using question tag on senior high school. The objective of this study are to find out types of errors that occur in using question tag, to find out the sources of errors that is made by tenth grade students at SMK Yapim Biru-Biru. This study used descriptive qualitative approach in analyzing the data. The data of this research are students answer sheet in using question tag. The result of this study, misformation occur as the highest error in using question tag, it is about 17 (56.7%) students and misordering occur as error in using question tag, it is about 8 (26.7%) students, the rest of error do not occur in this research. The source of error that is found in this research is context of learning, the rest source of error was not found in this research.